La Argentina tras la Ley de Identidad de Género: Autorrepresentaciones y argumentación en discursos de organizaciones LGBTTI+ - Manca, María Eugenia (Universidad Nacional de La Plata, 2021)
Despite the fact that in Argentina the Gender Identity Law is nine years old, it has not yet been possible to guarantee real social equality for the trans-transvestite community. This work analyzes the arguments of the main LGBTTI+ organizations in speeches in which they seek to account for this reality and justify the need to continue fighting for true inclusion. For this, we study how the construction of the ethos of each agent is articulated with other components of their argumentation to achieve an effective discourse.